Pengembangan Pariwisata Berbasis Budaya Lokal dengan Analisis Bibliometrik - Kasmin Kasmin; Lymbarski Caesariano; Mezi Julian; Gilang Fahreza (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2022)
Research on heritage diversity in Indonesia is still very rare, but for cultural heritage that is almost the same is found in several scopes or aspects of heritage in Indonesia. The problem that occurs in Indonesia is that the development of cultural heritage diversity (heritage diversity) still has a lot to be addressed, and the utilisation of functions that have not been maximised even though relics in the past or cultural heritage are part or characteristic of a nation or country including tribes. The search results using Publish or Perish (PoP) also show the lack of research journals on heritage diversity and cultural heritage. Through VOS Viewer, it was found that heritage diversity or cultural heritage is very potential to be developed and researched because it is still very minimal, especially regarding local culture. Culture-based tourism (Cultural Tourism) is a type of tourism activity that utilises culture as a tourist attraction visited by tourists in these tourist destinations, tourists will experience and learn about certain cultures. If the tourism industry can be managed properly, then tourism can ensure the preservation of nature and culture. In addition, tourism can also be a forum for employment for local communities around the tourist area. This research is qualitative research using Bibliometric analysis. Search results using Publish or Perish (PoP) and VOS Viewer with research objects in Pangandaran Regency, West Java Province.